Here's the question you clicked on:
sara1234
help me :(
I thinks it's: Simple interest: (1-(Current/initial))/years
can you show me how to do it step by step please so i can use it as an example?
It's simple interest rate, so, if it's X anual, in Y years it will be: Y*X In this case, we don't know X, but Y is 17 So its 17*X Then it's: 1+(17*X/100) (the /100 is because it's percent) Then We know the initial quantity, 2.567, was multiplied by: (1+(17*X/100)) and after this, we got 4443.48 So: 2567*(1+(17*X/100))=4443.48 Which is: Initial quantity(1+(Years*Interest Rate))=Final Quantity Interest rate is the X, and the other numbers are things we know. So, we insolate the X: 1+(17*X/100)=4443.48/2567 (17*X/100)=4443.48/2567-1 17*X=(4443.48/2567-1)*100 X=(4443.48/2567-1)*100/17
what do you think this is i can't tell very well